PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI DAN SISTEM PENGENDALIAN INTERNAL PEMERINTAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH DENGAN PENATAUSAHAAN ASET TETAP SEBAGAI VARIABEL INTERVENING (Studi pada BPKA Kota Bandung) - Faesal Fazlurahman; Nunuy Nur Afiah; Ivan Yudianto (Faculty of Economics and Business, Universitas Warmadewa, 2021)
The purpose of this study was to examine the effect of the use of information technology (IT) and the government's internal control system (SPIP) on the quality of local government financial statements (LKPD) by administering fixed assets as an intervening variable. the determination of the sample is determined by simple random sampling with the Slovin formula. The data source is primary data from the results of the questionnaire distributed and processed by path analysis. This study resulted in SPIP and the administration of fixed assets partially and simultaneously had a positive and significant effect on the quality of LKPD. However, the partial use of IT has a positive but not significant effect on the quality of LKPD. Then the partial and simultaneous use of IT and SPIP has a significant positive effect on the administration of fixed assets. In addition, the administration of fixed assets proved to be able to partially mediate the effect of the use of IT and SPIP on the quality of LKPD.